Coastal Surveying by Satellite and Helicopter Over the Channels of the Arcachon Basin - Le Ven, J. Y.; Chaumet-Lagrance, M.; Vallot, H. (The International Hydrographic Review, 2015)
During the winter season of 1990 and 1991, bathymetric surveys of the entrance channels to the Arcachon Basin (Fig. 1) by conventional surveying methods, i.e. from a small vessel, proved impossible to carry out; the roughness of the sea surface and the presence of dangerous shoals doomed all attempts to failure. Faced with the urgent need for reconnaissance surveys, the Directorate of Marine Development and Environment of the Port of Bordeaux proposed to the authorities responsible for safety in the channels of the Arcachon Basin that unconventional methods should be employed, using satellite and helicopter. Spatial remote sensing, which furnishes information that is rich as regards the morphology of the site but poor as regards bathymetry, finds that bathymetric surveying from a helicopter, which is poor in sounding points but rich as regards their spread over the area to be sounded, is an indispensable supplement to back up the bathymetry of the "pixels" composing the "Spot" image. The complementary nature of the two techniques proved to be most efficient in situations where reconnaissance was urgent but when meteorological conditions on site prevented conventional surveys being carried out using a boat.